(untitled) (Sustainability in Debate, 2016)
This paper identifies and analyzes different arenas that influence the conservation of the Brazilian Caatinga biome. It proposes a multi-method approach (situational analysis, document analysis and application of semi-structured interviews). It identifies three arenas that influence Caatinga conservation: the scientific arena, the economic-state arena and the sustainability arena. The interaction between different arena actors, at multiple levels of social organization, has improved the relevance of Caatinga. I was found that Caatinga conservation and sustainability has improved in the scientific and sustainability arenas, creating pressure on the economic-state arena and changing the ways of thinking about it and of acting upon it.